Hábitos alimentares e conservação do lobo-guará (Chrysocyon brachyurus) (Illiger, 1815) em um remanescente de Cerrado em Pirassununga – SP - Müller, Samara Thays Moreira (2016)
The Brazilian Cerrado, the second largest biome in the country, holds a high diversity of species. An important remnant is located at the Air Force Academy (AFA). Previous to this project, no biological studies had ever been carried out on AFA grounds and collecting extensive data in this area will be crucial for its conservation. An important step is to gather knowledge about species of conservation interest such as the maned wolf (Chrysocyon brachyurus), which is considered both a key-species and a flagship species for the Cerrado. It is estimated that over 90% of the maned wolf’s world population lives in Brazil, where the species is considered threatened and classified as “vulnerable”. Therefore, the protection of this species must be a priority in conservation projects in the country. It is also necessary that conservation efforts include a new way of looking at environmental challenges, in which humans are considered an integral part of the environment. The involvement of local communities can be decisive in the success or failure of conservation programs. In order to contribute to the conservation of the Cerrado, this project sought to verify the occurrence of the maned wolf in the Cerrado fragments at AFA and study the feeding habits of this species through the analysis of fecal samples. In addition, we tried to understand the perceptions of the workers at AFA regarding the Cerrado fragments and their associated wildlife, as well as the relationships between these people and the natural areas. The diet of the maned wolf was studied through the analysis of 61 fecal samples collected from October 2014 to September 2015. By frequency of occurrence, the queen palm coconut, arthropods and the wolf’s fruit were the most consumed items. Queen palm coconut, armadillos and lizards provided most of the consumed biomass. The niche breadth calculated through the standardized Levins’ index was 0,29 and chi-square and G tests showed there is seasonality in the diet. Our findings support the view that maned wolves are omnivorous. The items consumed were similar to the ones found in studies in more pristine areas, but there was a variation regarding the relative importance of food categories. The queen palm coconut and Arthropods were more frequent than in other studies, while birds, rodents and reptiles were found in smaller numbers. We investigated the perception of the personnel from AFA towards the Cerrado through the analysis of 40 semi structured interviews. The results indicate that most people do not have any knowledge regarding the fragments. This lack of knowledge is directly related to the attitudes that people have towards the Cerrado: most participants reported that they don’t feel any kind of connection with the biome. Finally, using the principles of critical environmental education as reference, we suggest a series of activities that can be employed to transform the relationship of these people with the environment. We emphasize that more studies should be done in this area, to which there is little information.